Relationship between the Sorghum's Physicochemical Attributes and the Flavor Components of Qing Stubble Daqu Baijiu - Linming SHI; Yanhong DU; Jianguang NIE; Hao TAN; Simai LI; Tingting LI (Shipin gongye ke-ji)
High-quality raw materials constitute a critical prerequisite for crafting premium Baijiu. This study aimed to explore the correlation between the physicochemical properties of sorghum and the quality of Qingcha Daqu Baijiu. Utilizing gas chromatography, this research analyzed the flavor compound profiles in sorghum variants 'JINZA 22' 'Northeast sorghum' and 'American sorghum'. Differential markers in Baijiu samples were identified through partial least squares discriminant analysis (PLS-DA). Further, the Mantel test was employed to probe the associations between sorghum's physicochemical attributes and the differential compounds in Baijiu. Additionally, Pearson correlation analysis elucidated the relationship between sorghum quality and alcohol yield. The findings revealed fifteen distinct biomarkers across the Baijiu samples. Notably, protein content in sorghum was significantly positively correlated with β-phenylethanol and 3-hydroxy-2-butanone in Baijiu samples (P<0.01), while amylopectin had the opposite effect. The lipid content significantly negative impacted acetic acid and ethyl acetate levels (P<0.01). Starch content was positively linked to alterations in β-phenylethanol and acetaldehyde concentrations (P<0.01), and tannin levels markedly negative-going affected acetaldehyde presence (P<0.01). The correlation study between sorghum quality and Baijiu yield demonstrated that the amylopectin and tannin content positively affected the alcohol yield (P<0.05), whereas the starch, amylose, protein content negatively affect the alcohol yield (P<0.05). Integrating sensory evaluations and flavor analysis, sorghum types HXGL-22 and HXGL-01, characterized by higher amylose and tannin contents, were found to enhance the quality of Qingcha Daqu Baijiu. These results provide a foundational basis for selecting raw materials for the industrial production of light-flavored Baijiu.